2024
DOI: 10.3390/ani14030399
|View full text |Cite
|
Sign up to set email alerts
|

eDNA-Based Early Detection Illustrates Rapid Spread of the Non-Native Golden Mussel Introduced into Beijing via Water Diversion

Wei Guo,
Shiguo Li,
Aibin Zhan

Abstract: The world’s largest water diversion, the South-to-North Water Transfer Project (SNWTP) in China, has created an “invasion highway” to introduce invasive golden mussels (Limnoperna fortunei) from the Yangtze River basin to Beijing. To examine the spread and colonization patterns of this newly introduced invasive species, we conducted comprehensive environmental DNA (eDNA)-based early detection and conventional field surveys across all water bodies in five river basins in Beijing from 2020 to 2023. Our results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The combination of DNA barcoding and eDNA sampling has been proven to be highly effective in detecting species of extremely low abundance. In China, Guo et al (2024) conducted comprehensive early detection based on eDNA and routine field surveys of all water bodies in five watersheds in Beijing from 2020 to 2023. L. fortunei successfully colonized in four of the five surveyed watersheds, with population densities ranging from 1 to 30 ind./m 2 across all 16 sites.…”
Section: Distribution and Population Dynamics Of Limnoperna Fortuneimentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of DNA barcoding and eDNA sampling has been proven to be highly effective in detecting species of extremely low abundance. In China, Guo et al (2024) conducted comprehensive early detection based on eDNA and routine field surveys of all water bodies in five watersheds in Beijing from 2020 to 2023. L. fortunei successfully colonized in four of the five surveyed watersheds, with population densities ranging from 1 to 30 ind./m 2 across all 16 sites.…”
Section: Distribution and Population Dynamics Of Limnoperna Fortuneimentioning
confidence: 99%
“…Figure 2d shows that mussels have the potential to invade other freshwater bodies around the world, except at higher latitudes, but it has been revealed that they can survive for some time at extreme temperatures (Guo et al, 2024;Xia et al, 2021). Therefore, without appropriate control measures, as human activity on the water increases and large-scale water facilities are built, which prompts the connectivity of watersheds, L. fortunei could probably be grown and detected globally.…”
Section: Distribution and Population Dynamics Of Limnoperna Fortuneimentioning
confidence: 99%